Kant - "Walker, Ralph C.S" (London, 2002)
Here is the first Kant-biography in English since Paulsen's and Cassirer's only full-scale study of Kant's philosophy. On a very deep level, all of Cassirer's philosophy was based on Kant's, and accordingly this book is Cassirer's explicit coming to terms with his own historical origins. It sensitively integrates interesting facts about Kant's life with an appreciation and critique of his works. Its value is enhanced by Stephen Körner's Introduction, which places Cassirer's Kant-interpretation in its historical and contemporary context."-Lewis White Beck "The first English translation (well done by James Haden) of a 60-year-old classic intellectual biography. Those readers who know Kant only through the first Critique will find their understanding of that work deepened and illuminated by a long explication of the pre-critical writings, but perhaps the most distinctive contribution is Cassirer's argument that the later Critiques, and especially the Critique of Judgment, must be understood not as merely applying the principles of the first to other areas but as subsuming the latter into a larger and more comprehensive framework."-Frederick J. Crown, The Key Reporter "Kant's Life and Thought is that rare achievement: a lucid and highly readable account of the life and work of one of the world's profoundest thinkers. Now for the first time available in an admirable English translation, the book introduces the reader to two of the finest minds in the history of philosophy."-Ashley Montagu
Keywords: "Kant, Immanuel"